Carta de Adolfo Porrata Doria a Roberto H. Todd - Todd, Roberto H.; Porrata Doria, Adolfo (My University, 1934)
Situación de los fondos y donativos para la viuda e hijos de Manuel A. Martínez Dávila.
Keywords: Martínez Dávila, Manuel A.,1883-1934; Barceló, Antonio R., 1868-1938